Isolasi gen kariogenik gtf BC Streptococcus mutans dari plak gigi anak (The isolation of Streptococcus mutans cariogenic gtf BC gene from children’s tooth plaque) - Yetty Herdiyati Soemantadiredja; Mieke Hemiawati Satari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The aim of this research was to prove that Streptococcus mutans isolated from children ‘s tooth plaque was cariogenic. Glf BC which is glycosiltransferase producer gene has had a role in caries development. This gene was isolated from Streptococcus mutans. The specimens were analyzed using Wizard Genomic DNA Purification Kit from Promega. In conclusion, S. mutans isolatedfrom children’s tooth plaque truly had cariogenic gtf BC gene.